Two new Metacephalus DeLong & Martinson, 1973 species (Hemiptera: Cicadellidae: Portanini) from Brazil and proposed synonymy with Paraportanus Carvalho & Cavichioli, 2009 - Souza, Stephanie Pereira De; Takiya, Daniela Maeda; Felix, Márcio (Zootaxa, 2017)
Synonymy of Paraportanus Carvalho & Cavichioli, 2009 with its senior synonym Metacephalus DeLong & Martinson, 1973 is proposed. Eleven species of Paraportanus are transferred to Metacephalus. Two new species of Metacephalus are described: Metacephalus adustus sp. nov. from Acre and Amazonas states, and Metacephalus sakakibarai sp. nov. from Amazonas and Roraima states. The first is diagnosed by its obliquely truncate pygofer posterior margin and aedeagus apex with pair of elongate and divergent spiniform processes. The second can be diagnosed by its rounded posterior pygofer margin and aedeagus apex with pair of elongate and parallel spiniform processes, directed posteroventrally. Metacephalus albocrux DeLong & Martinson, 1973 is newly recorded from Brazil. Metacephalus bicornis (Carvalho & Cavichioli, 2003) comb. nov. and Metacephalus jenniferae (Carvalho & Cavichioli, 2009) comb. nov. are newly recorded from Amazonas State; while Metacephalus facetus (Kramer, 1961) is newly recorded from Acre State.